Marketing Counselling Skills: Implications for Counsellor Education - Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article examines some of the differences between a counsellor's role as it is professionally defined and as it may be experienced in a school setting. In order to reduce these differences, the author suggests a model for marketing a professional counselling role. Steps for implementing the model are outlined along with the skills needed to successfully complete each step. Finally, counsellor educators are challenged to consider the need for teaching such social change models within their programmes.